Effects of Shuang Dan Ming Mu Capsule on Expression of VEGF-a, VEGF-b, VEGF-c and the VEGF receptor, Flk-1, in Diabetic Retinopathy Rats - Jun PENG; Kun PAN; Zheng-Rong LIU; Yu-Hui QIN; Qing-Hua PENG (KeAi Communications Co., Ltd., 2018)
ABSTRACT: Objective The effects of Shuang Dan Ming Mu capsule on expression of VEGF-a, VEGF-b, VEGF-c and the VEGF receptor, Flk-1, were examined in a diabetic retinopathy rats model.Methods Forty Sprague-Dawley (SD) rats were randomized into Groups A (blank), B (model), C (Shuang Dan Ming Mu) and D (positive control) group, with each group containing 10 rats and 20 eyes. Rats from groups B, C and D were administered one dose of 50 mg/kg streptozotocin (STZ) by tail vein injection to establish a diabetic rat model. One week after model preparation, medication was continuously administered by gavage. After gavage for 8 weeks, the animals were sacrificed and retinal expression of VEGF-a, VEGF-b, VEGF-c and Flk-1 was quantified by immunohistochemical analysis.Results At week 8 of drug administration after model preparation, the average protein expression grayscale values for VEGF-a, VEGF-b, VEGF-c and Flk-1 in the rats model, Shuang Dan Ming Mu and positive control groups were all lower than those in the normal group, while the mean optical density values were higher than those in the normal group. When the model group was compared to the normal group, the difference was extremely significant (P < 0.01). The mean grayscale values of VEGF-a, VEGF-b, VEGF-c and Flk-1 in the Shuang Dan Ming Mu and positive control groups were all higher than those in the model group, while the mean optical density values were lower than those in the model group (P <0.05 or 0.01).Conclusion Shuang Dan Ming Mu capsule can significantly decrease the expression of VEGF-a, VEGF-b, VEGF-c and Flk-1 in the retinas of diabetic model rats and exhibit some protective effects in their retinas. Keywords: Shuang Dan Ming Mu capsule, Diabetic rats model, VEGF-a, VEGF-b, VEGF-c, Flk-1